The Effect of Open Innovation on Sustainable Innovation Performance with Knowledge Sharing as an Intervening Variable: Case study Batik MSMEs Surakarta - Agus Suyatno; Saryadi Saryadi; Azzahra Salsa Nabila; Anis Wiji Lestari (Global Management: International Journal of Management Science and Entrepreneurship, 2024)
MSMEs are the business entities that contribute the most to employment in Indonesia. During the 1997 crisis, MSMEs were able to survive and become models in the case of economic crises. However, during the Covid-19 Pandemic, MSMEs are allegedly the most affected. The Indonesian government uses MSMEs to revive economic conditions that have been slumped during the Covid-19 Pandemic. In the midst of the boom, MSMEs in Indonesia, especially the invasion of imported products, need to find solutions in maintaining the sustainable performance of MSMEs. Innovation is needed by paying attention to open innovation and knowledge sharing so that MSMEs can rise again. This research is located in Surakarta, Indonesia with a saturated sample format of 50 Batik MSMEs. Data was obtained from Surakarta Batik MSMEs in the period of October to November 2024. Perseption measuarement in sustainable innovation peroformance, open innovation and knowledge sharing variable. The analysis tool uses path analysis equipped with t-test, F-test, determination coefficient, correlation test and Sobel test. The sobel test is used to determine the role of variable intervening. Before the analysis, the data is tested using data quality testing (validity and reliability). The findings shown that open innovation significant positive on knowledge sharing. Open innovation and knowledge sharing have a significant positive effect on sustainability innovation performance. Direct effect, more effective in improving the sustainable innovation performance. Another finding shows that although open innovation is directly more effective in influencing the sustainable innovation performance. Sobel test, show that knowledge sharing is more emphasized as an intervention although the influence is effective if it is carried out by choosing direct effect. The results of this study contribute to sustainable innovation performance in MSMEs Batik.